Postoperative Care of the Facial Plastic Surgery Patient—Forehead and Blepharoplasty - Neves, Jose Carlos; Medel Jiménez, Ramón; Arancibia Tagle, Diego; Vásquez, Luz María (Facial Plastic Surgery, 2018)
In any kind of surgery, postoperative care is essential for a good result, but especially when the matter at stake is facial plastic surgery. Despite having performed a perfect surgery, with the least amount of damage to the soft tissues and osteocartilaginous structures, minimal bleeding, and in terms of the surgical time, without adequate postoperative care our results can be affected considerably in the short and long run. Therefore, we must have very clear guidelines regarding postoperative care and the duties of our patients, which should be emphasized during the informed consent of the intervention. It is also essential to comment on the warning signs of postoperative complications, which need to be detected and treated in time to achieve the expected post-surgery results. Before being discharged from the hospital, the patient again receives the postoperative instructions, as well as receiving a paper copy to avoid any possible misunderstandings. In this article, we will detail the postoperative care and complications of brow lift and upper and lower blepharoplasty.
Keywords: brow lift; postoperative care; upper blepharoplasty; lower blepharoplasty